Scholars‘ view about approaches of teaching literature in efl classrooms (SCIENCE and SOCIETY, 2023)
Literature plays an important role in the development of English language, especially in improving com- munication skills, raising cultural awareness, and generating students’ motivation. This article deals with various of ap- proaches which can be helpful for teachers in conducting lessons and the ways of integrating literature in EFL classrooms.